Semiotic Analysis of the Song Kawanen Saur Composed by the Musical Group Jepang Jowo - Zulfa, Novita Hana; Sinaga, Syahrul Syah (Universitas Syiah Kuala, 2025)
This study aims to analyze the lyrics of the song